EMPLOYEE PERFORMANCE IMPROVEMENT IN HUMBLE LEADERSHIP, SERVANT LEADERSHIP AND EMPLOYEE INNOVATION BEHAVIOR - Dani Taupan Ramdani (Yayasan Education and Social Center, 2023)
The character of a good leader illustrates an important factor in the company's growth, where without the character of a good leader there will be obstacles in achieving the company's goals. The character of the leader can significantly influence the process of improving employee performance. In essence, the character and style of the leader are the causes that come from outside to be able to develop the personal performance of each employee. This research uses associative quantitative method assessment which is the method used in this study. The purpose of this study is to test hypotheses, namely studies that inform facts related to existing variables. Population of Total employees of PT. Indorama Petrochemicals as many as 276 people will be used as the population for the implementation of this research, using the slovin formula used as many as 163 employees. Humble leadership has a positive and insignificant effect on employee performance. shows a statistical t value of 1.020519. Where this value is smaller than 1.96 (∝=0.05). Servant leadership has a positive and significant effect on employee performance. shows the statistical t value of 2.200401. Humble leadership has a positive and significant effect on employee innovation behavior. shows the statistical t value of 2.664598. Servant leadership has a positive and significant effect on employee innovation behavior. shows a statistical t value of 4.476124 where this value is greater than 1.96 (∝=0.05). And Employee innovation behavior has a positive and significant effect on employee performance. shows the statistical t value of 2.769558